Identification and functional analysis of Trypanosoma cruzi genes that encode proteins of the glycosylphosphatidylinositol biosynthetic pathway. - Mariana S Cardoso (Public Library of Science (PLoS), 2013)
Background Trypanosoma cruzi is a protist parasite that causes Chagas disease. Several proteins that are essential for parasite virulence and involved in host immune responses are anchored to the membrane through glycosylphosphatidylinositol (GPI) molecules. In addition, T. cruzi GPI anchors have immunostimulatory activities, including the ability to stimulate the synthesis of cytokines by innate immune cells. Therefore, T. cruzi genes related to GPI anchor biosynthesis constitute potential new targets for the development of better therapies against Chagas disease. Methodology/principal findings In silico analysis of the T. cruzi genome resulted in the identification of 18 genes encoding proteins of the GPI biosynthetic pathway as well as the inositolphosphorylceramide (IPC) synthase gene. Expression of GFP fusions of some of these proteins in T. cruzi epimastigotes showed that they localize in the endoplasmic reticulum (ER). Expression analyses of two genes indicated that they are constitutively expressed in all stages of the parasite life cycle. T. cruzi genes TcDPM1, TcGPI10 and TcGPI12 complement conditional yeast mutants in GPI biosynthesis. Attempts to generate T. cruzi knockouts for three genes were unsuccessful, suggesting that GPI may be an essential component of the parasite. Regarding TcGPI8, which encodes the catalytic subunit of the transamidase complex, although we were able to generate single allele knockout mutants, attempts to disrupt both alleles failed, resulting instead in parasites that have undergone genomic recombination and maintained at least one active copy of the gene. Conclusions/significance Analyses of T. cruzi sequences encoding components of the GPI biosynthetic pathway indicated that they are essential genes involved in key aspects of host-parasite interactions. Complementation assays of yeast mutants with these T. cruzi genes resulted in yeast cell lines that can now be employed in high throughput screenings of drugs against this parasite.